Low‐temperature plasma for compositional depth profiling of crosslinking organic multilayers: comparison with C60 and giant argon gas cluster sources. (30th September 2014) - Muramoto, Shin; Rading, Derk; Bush, Brian; Gillen, Greg; Castner, David G.
<x xml:space="preserve">Abstract</x> RATIONALE For organic electronics, device performance can be affected by interlayer diffusion across interfaces. Time‐of‐flight secondary ion mass spectrometry (TOF‐SIMS) can resolve buried structures with nanometer resolution, but instrument artifacts make this difficult. Low‐temperature plasma (LTP) is suggested as a way to prepare artifact‐free surfaces for accurate determination of chemical diffusion. METHODS A model organic layer system consisting of three 1 nm delta layers of 2, 9‐dimethyl‐4, 7‐diphenyl‐1, 10‐phenanthroline (BCP) separated by three 30 nm layers of tris(8‐hydroxyquinolinato)aluminum (Alq3) was used to evaluate the effectiveness of LTP etching for the preparation of crater edge surfaces for subsequent compositional depth profile analysis. This was compared with depth profiles obtained using an instrument equipped with an argon cluster sputter source. RESULTS The quality of the depth profiles was determined by comparing the depth resolutions of the BCP delta layers. The full width at half maximum gave depth resolutions of 6.9 nm and 6.0 nm using LTP, and 6.2 nm and 5.8 nm using argon clusters. In comparison, the 1/e decay length of the trailing edge gave depth resolutions of 2.0 nm and 1.8 nm using LTP, and 3.5 nm and 3.4 nm using argon clusters. CONCLUSIONS The comparison of the 1/e decay lengths showed that LTP can determine the thickness and composition of the buried structures without instrument artifacts. Although it does suffer from contaminant deposition, LTP was shown to be a viable option for preparing crater edges for a more accurate determination of buried structures. Copyright © 2014 John Wiley & Sons, Ltd.